2018
DOI: 10.1590/18069657rbcs20170016
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Community Structure and Diversity in Cut Flower Cultures Under Conventional and Ecological Management

Abstract: Microorganisms are excellent soil quality indicators because their properties within the soil community change quickly in response to changes in the surrounding environment. The aim of this study was to determine if the structure and diversity of soil bacterial and fungal communities were useful for discriminating cut flower cultures under conventional (CM), ecological (EM), and intermediate (IM) management practices.Results obtained by PCR-DGGE revealed that bacteria had lower similarity in structure and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(20 reference statements)
0
4
0
1
Order By: Relevance
“…Existing studies have shown that soil microbial diversity differed significantly among different grassland community type ( Qi et al, 2021 ), and the more suitable the habitat conditions (High total nitrogen and organic carbon content and suitable soil pH, etc. ), the higher the diversity was Santamaría et al ( Santamaría et al, 2018 ). Besides, the diversity of different soil bacterial communities was mainly influenced by pH, organic matter, alkaline nitrogen and effective phosphorus content ( Dunbar et al, 2002 ; Roy et al, 2020 ; Jiang et al, 2021 ), while soil pH and organic matter content played a decisive role in the structure of different soil fungal communities ( Guo et al, 2021 ; Shang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 97%
“…Existing studies have shown that soil microbial diversity differed significantly among different grassland community type ( Qi et al, 2021 ), and the more suitable the habitat conditions (High total nitrogen and organic carbon content and suitable soil pH, etc. ), the higher the diversity was Santamaría et al ( Santamaría et al, 2018 ). Besides, the diversity of different soil bacterial communities was mainly influenced by pH, organic matter, alkaline nitrogen and effective phosphorus content ( Dunbar et al, 2002 ; Roy et al, 2020 ; Jiang et al, 2021 ), while soil pH and organic matter content played a decisive role in the structure of different soil fungal communities ( Guo et al, 2021 ; Shang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 97%
“…The types of operations in farmland, such as effective management, the tillage regime, and fertilization practice, have been found to have an impact on soil microorganisms. The microbial community structure and diversity of three different management practices (conventional, ecological, and intermediate) of cut flower cultures were investigated, and it was found that the bacterial community structure differed considerably among the three management practices, indicating that it can effectively monitor the soil quality change by different management practices of cut flower cultures [ 68 ]. In addition to management practices, the tillage regime has also been found to influence the soil microbial community.…”
Section: Microbial Indicators In Artificial Ecosystemsmentioning
confidence: 99%
“…PCR cycling temperatures for the 433 bp fragment amplification with the 968F and 1401R primers were as follows: 94 °C for 3 min (1 cycle); 94 °C for 50 s, 48 °C for 20 s, and 72 °C for 45 s (30 cycles); followed by a final step at 72 °C for 5 min. The DGGE analysis of the 433 pb PCR products was performed according to Santamaría et al [38], using a different denaturing gradient (37 % to 65 %) and an electrophoresis run time of 17 h at 35 V and 60 °C.…”
Section: Dna Extraction and Molecular Analysismentioning
confidence: 99%